(untitled) (Journal of the College of Basic Education, 2023)
The world, including our Arab society, has witnessed great changes as a result of the tremendous scientific progress that generated a revolution Information transmitted by individuals in all parts of the world through the satellite network and the Internet, leaving great impacts depth on their values ​​and orientations, despite the peculiarities that characterize societies in terms of its cultural and social framework and the nature of its education systems. Nevertheless, there were some manifestations of Transformation and change in various areas of life